PENERAPAN STANDAR OPERASIONAL PROSEDUR KARYAWAN BANQUET SECTION DI THE ZURI HOTEL PEKANBARU - Ramadhan, Hibatullah; Sidiq, Rd. Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The focus of this research is how to apply standard operating procedures in improving employee work in the banquet section of The Zuri Hotel Pekanbaru. The purpose of this research is to improve the standard operating procedures of existing work so that employees in the banquet section. This is done to improve its quality and be able to provide effective services and be able to carry out work activities according to the steps that have been determined by management. The approach used in research is a qualitative descriptive approach. Data collection techniques used are (1) observation (2) interviews (3) documentation. Based on the results of the study, it shows: (1) employees do not fully understand the contents of the soup that must be carried out so that it is not optimal in its implementation, (2) there is still a lack of evaluation from management on the performance of banquet section employees for implementing SOP. Keywords: Implementation, Standard Operating Procedures, Banquet Section